Sexual Behaviour Change on Youth in Digitalized World - Rey Quincy; Kammuraed Manduza (Newinera Publisher, 2021)
This article discusses the characteristics of adolescents and the influence of social media on adolescent sexual behavior. The millennial generation's communication style is also extremely open in comparison to earlier generations, in terms of obsessive use of social media, and every aspect of life is heavily affected by technology advancements and places a premium on money. Sexual harassment on the Internet is harassment that comes to light via a large yet ineffective reporting and management process. Sexual harassment on social media is becoming an increasingly public issue, according to a new study by Google Form. The study gathered information from 104 respondents with birth years ranging from 1980 to 2000 who engaged in a poll